Highly Efficient Rhodium-Catalyzed Transfer Hydrogenation of Nitroarenes into Amines and Formanilides - Wei, Yawen; Wu, Jianjun; Xue, Dong; Wang, Chao; Liu, Zhaotie; Zhang, Zhuozhuo; Chen, Guangfu; Xiao, Jianliang (Synlett, 2014)
An efficient and selective rhodium-catalyzed transfer hydrogenation of nitroarenes with formic acid as the hydrogen source to give amines or formanilides has been developed. The addition of iodide ion accelerates the reaction, which can take place at room temperature.
Keywords: reduction; hydrogenation; nitroarenes; amines; amides; catalysis; rhodium